2015
DOI: 10.1177/2047487315604836
|View full text |Cite
|
Sign up to set email alerts
|

The combined exercise stress echocardiography and cardiopulmonary exercise test for identification of masked heart failure with preserved ejection fraction in patients with hypertension

Abstract: Background: Heart failure with preserved ejection fraction (HFpEF) is commonly associated with hypertension (HTN). However, resting echocardiography (ECHO) can underestimate the severity of disease. Exercise stress echocardiography (ESE) and the cardiopulmonary exercise testing (CPX) appeared to be useful tests in dynamic assessment of HFpEF. The value of combined exercise stress echocardiography cardiopulmonary testing (ESE-CPX) in the identification of masked HFpEF is still undetermined. Objective: The purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 40 publications
(54 reference statements)
2
62
0
1
Order By: Relevance
“…They concluded that the VE/ VCO2 slope could be a reliable test to diagnose HFpEF in an early stage, but they did not investigate the possible association between VE/VCO2 and mortality. 22 Hemodynamic measurements in our study showed that increased VE/VCO2 slope was associated with increased mPAP and PVR. Of note, no association was observed between VE/ VCO2 slope and PWCP.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…They concluded that the VE/ VCO2 slope could be a reliable test to diagnose HFpEF in an early stage, but they did not investigate the possible association between VE/VCO2 and mortality. 22 Hemodynamic measurements in our study showed that increased VE/VCO2 slope was associated with increased mPAP and PVR. Of note, no association was observed between VE/ VCO2 slope and PWCP.…”
Section: Discussionsupporting
confidence: 54%
“…A few others studied the value of CPX in patients with HFpEF. [20][21][22] Guazzi et al compared CPX parameters with multiple variables between an HFrEF and an HFpEF population. 20 Although that study showed that the VE/VCO2 slope represents HFpEF severity, no relationship between the VE/VCO2 slope and mortality was studied.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous variables from both CPX and Doppler echocardiography at peak exercise (eg, E/e´, peak V slope) were significantly different between subjects with and without HF with preserved EF. 105 These findings demonstrate the potential utility of CPX and exercise Doppler echocardiography in identifying HF with preserved EF at an earlier time point, prompting more aggressive medical management and improving clinical outcome. 106 We recognize the combined CPX-Doppler echocardiographic assessments do not hold broad applicability at this time.…”
Section: Synergistic Assessments: Cpx and Doppler Echocardiographymentioning
confidence: 60%
“…Obesity can lead to structural and functional worsening of the cardiovascular and pulmonary system [17, 18], as well as a reduction of the oxidative capacity of skeletal muscles [19]. Cardiopulmonary functional capacity provides diagnostic and prognostic information in a wide variety of clinical settings [20, 21]. …”
Section: Introductionmentioning
confidence: 99%